(untitled) (Journal of Tourism and Himalayan Adventures, 2021)
Local porters who haul burdens for trekkers are understudied and underappreciated for the labour they do in Nepal. Their susceptibility to Acute Mountain Sickness (AMS) along with the weight of the loads they haul and carry in return for meagres payment, contribute to the difficulties of their very austere and under-resourced employment. They are frequently underpaid for their efforts. Acknowledgement by government organizations and trekking business owners could make their employment more viable by giving them a higher wage in spite of their occupation struggles. Data was gathered from 31 porters completing instruction at a Nepali Porters’ training establishment, based in Kathmandu, Nepal. The research used semi-structured in-depth interviews. Participants participated in a 45-60-minute interview, which was recorded at the field site. All the interviews were documented and then transcribed into English by a bilingual Nepali PhD student. The data was coded using a hierarchical, thematic coding structure approach. Findings showed that porters knew about and had experienced AMS, and that their work of carrying heavy cargoes for trekkers and trekking companies were often not compliant with prescribed kilogram load limits.